Safety of intrathecal autologous adipose-derived mesenchymal stromal cells in patients with ALS. (22nd November 2016) - Staff, Nathan P.; Madigan, Nicolas N.; Morris, Jonathan; Jentoft, Mark; Sorenson, Eric J.; Butler, Greg; Gastineau, Dennis; Dietz, Allan; Windebank, Anthony J.
Abstract : Objective: To determine the safety of intrathecal autologous adipose-derived mesenchymal stromal cell treatment for amyotrophic lateral sclerosis (ALS). Methods: Participants with ALS were enrolled and treated in this phase I dose-escalation safety trial, ranging from 1 × 10 7 (single dose) to 1 × 10 8 cells (2 monthly doses). After intrathecal treatments, participants underwent standardized follow-up, which included clinical examinations, revised ALS Functional Rating Scale (ALSFRS-R) questionnaire, blood and CSF sampling, and MRI of the neuroaxis. Results: Twenty-seven patients with ALS were enrolled and treated in this study. The safety profile was positive, with the most common side effects reported being temporary low back and radicular leg pain at the highest dose level. These clinical findings were associated with elevated CSF protein and nucleated cells with MRI of thickened lumbosacral nerve roots. Autopsies from 4 treated patients did not show evidence of tumor formation. Longitudinal ALSFRS-R questionnaires confirmed continued progression of disease in all treated patients. Conclusions: Intrathecal treatment of autologous adipose-derived mesenchymal stromal cells appears safe at the tested doses in ALS. These results warrant further exploration of efficacy in phase II trials. Classification of evidence: This phase I study provides Class IV evidence that in patient with ALS, intrathecal autologous adipose-derived mesenchymal stromal cell therapy is safe.